2007
DOI: 10.1123/tsp.21.2.191
|View full text |Cite
|
Sign up to set email alerts
|

How Youth-Sport Coaches Learn to Coach

Abstract: Researchers have investigated how elite or expert coaches learn to coach, but very few have investigated this process with coaches at the recreational or developmental-performance levels. Thirty-six youth-sport coaches (ice hockey, soccer, and baseball) were each interviewed twice to document their learning situations. Results indicate that (a) formal programs are only one of the many opportunities to learn how to coach; (b) coaches’ prior experiences as players, assistant coaches, or instructors provide them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
180
3
39

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 208 publications
(251 citation statements)
references
References 33 publications
29
180
3
39
Order By: Relevance
“…While this study was the first to link childhood experiences outside of sport (i.e., family and school) with learned coaching approaches, the results also concur with a number of findings from other studies on how coaches learn through their athletic experiences (Cushion et al 2003;Demers, 2004;Lemyre et al 2007;Wright et al 2007). Smoll, Smith, and Cumming (2007) found that the behaviors of coaches influence their athletes' attitudes and perceptions towards their coaches, themselves, and their sport experiences.…”
Section: Journal Of Coaching Educationsupporting
confidence: 73%
See 1 more Smart Citation
“…While this study was the first to link childhood experiences outside of sport (i.e., family and school) with learned coaching approaches, the results also concur with a number of findings from other studies on how coaches learn through their athletic experiences (Cushion et al 2003;Demers, 2004;Lemyre et al 2007;Wright et al 2007). Smoll, Smith, and Cumming (2007) found that the behaviors of coaches influence their athletes' attitudes and perceptions towards their coaches, themselves, and their sport experiences.…”
Section: Journal Of Coaching Educationsupporting
confidence: 73%
“…Research also indicates that a coach's previous experience as an athlete is an important way that coaches learn how to coach because these experiences help them learn about the subculture of the sport, enabling them to interact with others involved in the sport, such as athletes, coaches, and parents (Cushion et al 2003;Stephenson & Jowett, 2009;Lemyre, Trudel, & Durand-Bush, 2007). For Cushion and colleagues (2003), athletic experiences influenced future coaches' familiarity with coaching, collective understandings, and shared meanings and "such formative experiences carry far into a coach's career and provide a continuing influence over perspectives, beliefs, and behaviours," (p. 218).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the UK, none of the expert and elite coaches interviewed by Sproule (2009) or Chesterfield et al (2010) felt that formal education had any impact on their practice. Such findings are echoed with amateur coaches in Canada (Lemyre et al 2007) and Portugal (Mesquita et al 2010) and are further supported by a common posture in the literature that dismisses formal learning as rigid, out-dated and largely irrelevant to coach development (cf. Cassidy et al 2006;Roberts 2010;Chesterfield et al 2010;Nash and Sproule 2011;Nelson et al 2012).…”
Section: Coach Learningmentioning
confidence: 69%
“…For example, formal education has been found to be enjoyable and effective under certain conditions: namely, where coaches are less educated or at an earlier stage of development (Lemyre et al 2007;Vargas-Tonsing 2007;Erickson et al 2008;Mesquita et al 2010;Nash and Sproule 2011), and where courses are more open and discursive in pedagogical approach (McCullick et al 2005;Cassidy et al 2006;Piggott 2012). In their study of Canadian coaches engaged in the NCCP, Erickson et al (2008) found that coaches who aspired to higher levels of accreditation were more prepared to learn independently, whereas less ambitious coaches had a clear preference for formal learning.…”
Section: Coach Learningmentioning
confidence: 99%
“…O recurso a imitação tem sido utilizado em grande parte por profissionais em início de carreira (LEMYRE; TRUDEL; DURAND-BUSH, 2007;RAMOS et al, 2011).…”
Section: Discussão As Crenças a Respeito Do Conhecimento Pedagógicounclassified